Pre-Constitutional Law and Constitutions: Spanish Colonial Law and the Constitution of Cádiz - M.C. Mirow (Washington University Global Studies Law Review, 2013)
The Spanish Constitution of Cádiz of 1812 (“Constitution”) has recently attracted the attention of constitutionalists and legal historians for its role as an essential step in the development of both world and Latin American constitutionalism. The interest in the Constitution has increased due to its 2012 bicentennial and the rolling independence bicentennials of the Latin American republics. There is a well-documented connection between the events leading to the Constitution’s implementation throughout the Spanish Empire and both initial Latin American independence movements and subsequent constitutional texts and practices. There are fewer studies, however, concerning the pivotal role the extant Spanish colonial law (derecho indiano) played in these events. Instead of exploring the effect produced by the Constitution in subsequent constitutional developments, this study examines the way existing law informed the constitutional process in Cádiz and shaped the Constitution itself. More specifically, this article examines the role and function of Spanish colonial law as related to both the constitutional debates and the text itself. It seeks to explore the important place Spanish colonial law had in the Constitution’s construction, the way it limited the scope of the Constitution, and the way the Constitution, in turn, shaped Spanish colonial law.
Keywords: Cadiz; Spain; Latin America; constitutionalism; colonial law; derecho indiano